Association Between Graft Choice and 6-Year Outcomes of Revision Anterior Cruciate Ligament Reconstruction in the MARS Cohort. Issue 10 (August 2021) - ; Wright, Rick W.; Huston, Laura J.; Haas, Amanda K.; Pennings, Jacquelyn S.; Allen, Christina R.; Cooper, Daniel E.; DeBerardino, Thomas M.; Dunn, Warren R.; Lantz, Brett (Brick) A.; Spindler, Kurt P.; Stuart, Michael J.; et al.
Background: Although graft choice may be limited in the revision setting based on previously used grafts, most surgeons believe that graft choice for anterior cruciate ligament (ACL) reconstruction is an important factor related to outcome. Hypothesis: In the ACL revision setting, there would be no difference between autograft and allograft in rerupture rate and patient-reported outcomes (PROs) at 6-year follow-up. Study Design: Cohort study; Level of evidence, 2. Methods: Patients who had revision surgery were identified and prospectively enrolled in this cohort study by 83 surgeons over 52 sites. Data collected included baseline characteristics, surgical technique and pathology, and a series of validated PRO measures. Patients were followed up at 6 years and asked to complete the identical set of PRO instruments. Incidence of additional surgery and reoperation because of graft failure were also recorded. Multivariable regression models were used to determine the predictors (risk factors) of PROs, graft rerupture, and reoperation at 6 years after revision surgery. Results: A total of 1234 patients including 716 (58%) men were enrolled. A total of 325 (26%) underwent revision using a bone-patellar tendon-bone (BTB) autograft; 251 (20%), soft tissue autograft; 289 (23%), BTB allograft; 302 (25%), soft tissue allograft; and 67 (5%), other graft. Questionnaires and telephone follow-up for subsequent surgery information were obtained for 809 (66%) patients, while telephone follow-up was only obtained for an additional 128 patients for the total follow-up on 949 (77%) patients. Graft choice was a significant predictor of 6-year Marx Activity Rating Scale scores ( P = .024). Specifically, patients who received a BTB autograft for revision reconstruction had higher activity levels than did patients who received a BTB allograft (odds ratio [OR], 1.92; 95% CI, 1.25-2.94). Graft rerupture was reported in 5.8% (55/949) of patients by their 6-year follow-up: 3.5% (16/455) of patients with autografts and 8.4% (37/441) of patients with allografts. Use of a BTB autograft for revision resulted in patients being 4.2 times less likely to sustain a subsequent graft rupture than if a BTB allograft were utilized ( P = .011; 95% CI, 1.56-11.27). No significant differences were found in graft rerupture rates between BTB autograft and soft tissue autografts ( P = .87) or between BTB autografts and soft tissue allografts ( P = .36). Use of an autograft was found to be a significant predictor of having fewer reoperations within 6 years compared with using an allograft ( P = .010; OR, 0.56; 95% CI, 0.36-0.87). Conclusion: BTB and soft tissue autografts had a decreased risk in graft rerupture compared with BTB allografts. BTB autografts were associated with higher activity level than were BTB allografts at 6 years after revision reconstruction. Surgeons and patients should consider this information when choosing a graft for revision ACL reconstruction.